THE EFFECT OF CHARACTERISTICS AND ENTREPRENEURSHIP OF THE STUDENTS 'INTEREST IN VOCATIONAL SCHOOL WITH MOTIVATION AS A VARIABLE OF MEDIATION - Imam Faisal (Dinasti Publisher, 2020)
The background of this study is the high unemployment rate in Indonesia and the biggest contributor to unemployment in Indonesia is vocational graduates, this study aims to determine the effect of entrepreneurial characteristics, knowledge and motivation on entrepreneurial interest both simultaneously and partially, with entrepreneurship motivation as a mediating variable. This type of research is causality by clicking g unakan approach is quantitative. The study population was students of SMK Global Informatika. The sampling technique uses probability sampling method. The number of samples determined was 95 respondents. Methods of data analysis using structural equation model with descriptive statistical tests, the validity and reliability of data and hypothesis testing using SmartPLS program Version 3. 0 for Windows. B erdasarkan test results determination coefficient result in the value of R -S quare respectively at 0 , 489 to 0,646 for the motivation and interest in entrepreneurship , it refers k an effect of variable characteristics and entrepreneurial knowledge on the motivation of entrepreneurship of 48.9 per cent, then the influence of the characteristics , entrepreneurial knowledge and motivation was 64.6 percent, while the remaining 51.1 percent and 35.4 percent were influenced by other factors not examined . The results of this study indicate that : (1) entrepreneurial characteristics and knowledge have a significant positive effect on entrepreneurial motivation ; (2) the characteristics, knowledge and motivation of entrepreneurship have a significant positive effect directly on entrepreneurial interest ; (3) When the characteristics and entrepreneurial knowledge mediated by variab el entrepreneurship motivation , both variables have the effect of partial mediation interest in entrepreneurship.